Key determinants of global land-use projections - Stehfest, Elke; Zeist, Willem-Jan van; Valin, Hugo; Havlik, Petr; Popp, Alexander; Kyle, Page; Tabeau, Andrzej; Mason-D'Croz, Daniel; Hasegawa, Tomoko; Bodirsky, Benjamin L.; Calvin, Katherine; Doelman, Jonathan C; et al. (Springer, 2019)
Land use is at the core of various sustainable development goals. Long-term climate foresight studies have structured their recent analyses around five socio-economic pathways (SSPs), with consistent storylines of future macroeconomic and societal developments; however, model quantification of these scenarios shows substantial heterogeneity in land-use projections. Here we build on a recently developed sensitivity approach to identify how future land use depends on six distinct socio-economic drivers (population, wealth, consumption preferences, agricultural productivity, land-use regulation, and trade) and their interactions. Spread across models arises mostly from diverging sensitivities to long-term drivers and from various representations of land-use regulation and trade, calling for reconciliation efforts and more empirical research. Most influential determinants for future cropland and pasture extent are population and agricultural efficiency. Furthermore, land-use regulation and consumption changes can play a key role in reducing both land use and food-security risks, and need to be central elements in sustainable development strategies.